Class, Opportunity and the Lesser Minds Problem: A Ragged University Response - Dunedin, Alex (PRISM: Casting New Light on Learning, Theory and Practice, 2018)
In this paper psychological research is used to develop a framework in which we can place notions of class in terms of relative dehumanisation as ingroups and outgroups to understand how opportunities are afforded to some and not to others, with categorical identities set up on the basis of inclusion or exclusion from cultural production. It draws upon political economy as a Social Science to examine how resulting culture reinforces relative advantage and disadvantage through finance as a mechanism which dispossesses the most disadvantaged from their inherent human capital as wealth appropriated by the advantaged. It introduces education as necessarily a project of social justice, with the Ragged University as a model in education consistent with human development and designed to function for the least advantaged under the hostile sociology of artificial scarcity.